Original paper21-year retrospective study of the prevalence of Scopulariopsis brevicaulis in patients suspected of superficial mycoses - B. Macura, Anna; Skóra, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: In the genus Scopulariopsis, Scopulariopsis brevicaulis is the most common aetiological agent of infections in humans. It usually affects nails and is one of the commonest moulds associated with onychomycoses. Other forms of infections (skin, subcutaneous, deep tissues, and disseminated infections) have also been described. Aim: To examine the prevalence of S. brevicaulis in clinical materials obtained from patients suspected of keratinized tissues mycoses. Material and methods : The analysis of the prevalence of S. brevicaulis in clinical specimens was based on mycological test's results carried out for patients who were referred with a suspicion of superficial mycoses to the Department of Mycology, Chair of Microbiology, Jagiellonian University Medical College from 1992 till 2012. Results : In the years 1992–2012 16,815 clinical samples (nail scrapings, nail swabs, skin scrapings, skin swabs, hair) were collected. Pathogenic fungi were detected in 7193 samples and S. brevicaulis was present in 255 (3.5%). The prevalence of S. brevicaulis in males and females was comparable. The species was most often isolated from toenails (80%), both from males and females. In the analysed period we observed a decrease in the prevalence of S. brevicaulis . In most cases (60%) S. brevicaulis occurred alone in 40% of S. brevicaulis positive cultures, other fungi were also isolated. The fungi most frequently isolated with S. brevicaulis were Trichophyton rubrum, T. mentagrophytes, Penicillium sp., Candida sp., and Aspergillus sp. Conclusions : Scopulariopsis brevicaulis is not a common cause of superficial fungal infections of keratinized tissues, but is a typical mould associated with toenail onychomycosis. A proper identification of this species in onychomycoses is essential for the implementation of effective antifungal therapy.